2018
DOI: 10.1128/iai.00651-17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-Like Receptor 2 by Dendritic Cells Is Essential for the DnaJ-ΔA146Ply-Mediated Th1 Immune Response against Streptococcus pneumoniae

Abstract: The fusion protein DnaJ-ΔA146Ply could induce cross-protective immunity against pneumococcal infection via mucosal and subcutaneous immunization in mice in the absence of additional adjuvants. DnaJ and Ply are both Toll-like receptor 4 (TLR4) but not TLR2 ligands. However, we found that TLR2 mice immunized subcutaneously with DnaJ-ΔA146Ply showed significantly lower survival rates and higher bacterial loads in nasal washes than did wild-type (WT) mice after being challenged with pneumococcal strain D39 or 19F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…ClusPro and DimPlot results of DnaJ and HLA-DRB1*01:01 (the most common binding allele in the Iran population) docking complex showed the lowest energy binding of -809.63 Kcal/mol and 63 cluster members indicating good binding affinity and coupling of this protein with human MHCII via 11 hydrogen bonds. It was reported that DnaJ contributes to the activation of bone marrow-derived dendritic cells (BMDCs) and phagocytosis of macrophage, leading to the development of innate, humoral and cellular immunities through Toll-like receptors 4 and 2 (TLR-4 and TLR-2) [20,21,48]. For a more detailed understanding of the amino acid residues of DnaJ involved in the interacting interface with TLRs molecules, molecular docking was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ClusPro and DimPlot results of DnaJ and HLA-DRB1*01:01 (the most common binding allele in the Iran population) docking complex showed the lowest energy binding of -809.63 Kcal/mol and 63 cluster members indicating good binding affinity and coupling of this protein with human MHCII via 11 hydrogen bonds. It was reported that DnaJ contributes to the activation of bone marrow-derived dendritic cells (BMDCs) and phagocytosis of macrophage, leading to the development of innate, humoral and cellular immunities through Toll-like receptors 4 and 2 (TLR-4 and TLR-2) [20,21,48]. For a more detailed understanding of the amino acid residues of DnaJ involved in the interacting interface with TLRs molecules, molecular docking was performed.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that DnaJ contributes to the activation of bone marrow-derived dendritic cells (BMDCs) and phagocytosis of macrophage, leading to the development of innate, humoral and cellular immunities through Toll-like receptors 4 and 2 (TLR4 and TLR2) [20,21,48]. For a more detailed understanding of the amino acid residues of DnaJ involved in the interacting interface with TLRs and MHC molecules, molecular docking was performed.…”
Section: Determination Of the Potential Regions Involved In Dnaj-tlrs...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the crystal structure of the obtained TLR4 did not initially include any docked molecule, three (3) known TLR4-agonists: enzyme lumazine synthase from Brucella spp. 128 , resuscitation-promoting factor (Rpf) E from Mycobacterium tuberculosis 129 , and fusion protein DnaJ- A146Ply from Streptococcus pneumoniae 130 were docked to the TLR4 crystal structure to serve as control. The G values and molecular interactions of the TLR4-agonists complexes were compared to the ASFV vaccine construct.…”
Section: Methodsmentioning
confidence: 99%
“…However, DnaJ-ΔA146Ply, which is a genetic fusion of DnaJ and a ply mutant (ΔA146Ply), induces protection of mice in a TLR2-dependent manner. Furthermore, TLR2 deficiency reduces the ability of DnaJ-ΔA146Ply to induce Th1 type immune response (60). Another protein from S. pneumoniae , endopeptidase O (PepO) exhibits TLR2 and TLR4 agonist properties.…”
Section: Introductionmentioning
confidence: 99%